The relationship between transformational leadership, organizational culture and employees job performance of Abu Dhabi National Oil Company - Abdullah Al Dhanhani, Aishah (2020)
Optimum job performance is often the primary result that organization seek to achieve. Available literatures have shown that leaders’ behavior shape organizational culture which lead to optimum job performance, thereby contributing to organizational success. However, despite compelling evidence on previous studies on the effects of transformational leadership and organizational culture and employees’ performance, there is an overwhelming lack of insights regarding the dynamics and interplay of transformational leadership and employees’ job performance in Middle Eastern countries such as UAE. Likewise, based on preliminary interview conducted, employees’ job performance at Abu Dhabi oil and gas companies is not satisfactory. Therefore, this research examined the effect of transformational leadership on job performance of employees at Abu Dhabi National Oil Company, with the mediating role of organizational culture. In this quantitative research work, a structured questionnaire with a 5-point Likert scale was used as the instrument for data collection from the total of 450 respondents from Abu Dhabi National Oil Company. The validity and reliability of the measurement and structural models were ascertained. The Partial Least Square Structural Equation Modeling (PLS-SEM) was used to test the hypotheses. Findings of this research revealed a moderate level of transformational leadership, organizational culture and job performance. Furthermore, the result reveals that there was a substantial mediating effect of organizational culture on the relationship between transformational leadership style and job performance. The results add to the existing literature by incorporating variables that might improve job performance. It is recommended that UAE oil and gas companies to enhance their organizational culture by hiring managers with transformational leadership qualities. Through this, employees’ job performance can be improved, leading to a positive and significant effect on overall organizational performance. The research also addressed the implication of practices and future research.